2004
DOI: 10.1029/2003ja009972
|View full text |Cite
|
Sign up to set email alerts
|

Nadir observations of sprites from the International Space Station

Abstract: [1] The experiment LSO (Lightning and Sprite Observations) is dedicated to the optical study, from the International Space Station, of sprites occurring in the upper atmosphere above thunderstorms. The objectives were to study these phenomena and to validate a new measurement concept for future measurements of sprites from space at the nadir. The first measurements were performed in the frame of the flight of the French Astronaut Claudie Haigneré (mission Andromède) in October 2001. Observations were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 36 publications
0
59
0
1
Order By: Relevance
“…For example, ELF waveform recording and triangulation by the Schumann Resonance method has been used to study the characteristics of TLEs' parent lightning, especially the charge moment change and the polarity (Huang et al 1999; Sato and Fukunishi 2003;Cummer 2006). Space observation was first analyzed by Boeck et al (1995Boeck et al ( , 1998, followed by man-operated observation onboard the tragic space shuttle mission STS-107 (Yair et al 2004), and a nadir observation from the International Space Station (ISS, Blanc et al 2004). Space observation is able to carry out global observations and overcome geographical limitations, especially for oceanic regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ELF waveform recording and triangulation by the Schumann Resonance method has been used to study the characteristics of TLEs' parent lightning, especially the charge moment change and the polarity (Huang et al 1999; Sato and Fukunishi 2003;Cummer 2006). Space observation was first analyzed by Boeck et al (1995Boeck et al ( , 1998, followed by man-operated observation onboard the tragic space shuttle mission STS-107 (Yair et al 2004), and a nadir observation from the International Space Station (ISS, Blanc et al 2004). Space observation is able to carry out global observations and overcome geographical limitations, especially for oceanic regions.…”
Section: Introductionmentioning
confidence: 99%
“…The fi rst imaging of sprites from the space shuttle during the early 1990s showed that they were occurring over Argentina [Boeck et al, 1995;Lyons and Williams, 1993], and Blanc et al [2004] reported observing fi ve sprites over this region from the International Space Station during October 2002.…”
Section: Fig 2 Holocene Stratigraphy and Calibrated Radiocarbon Datmentioning
confidence: 99%
“…The first imaging of sprites from the space shuttle during the early 1990s showed that they were occurring over Argentina [Boeck et al, 1995;Lyons and Williams, 1993], and Blanc et al [2004] reported observing five sprites over this region from the International Space Station during October 2002.…”
Section: The February 2006 Thunderstormsmentioning
confidence: 99%